(untitled) (Research, Society and Development, 2020)
This study presents the results of the analysis of the processes of a dairy industry, where the functions and activities developed expose workers to different environmental risk factors, which impact safety and health performance. For example, there are activities that require intense and repetitive efforts, work performed at abnormal temperatures (cold and heat) and noise, contact with mechanical risk factors that can lead to injury, thus making workers susceptible to accidents and diseases . This study aimed to analyze the processes of a dairy, identify the risk factors (hazards) and propose control measures to eliminate and / or reduce the risks associated with the safety and health of workers. The work methodology used was a qualitative approach through knowledge of the productive processes of a medium-sized dairy, as well as interviews with workers. Analyzes of the information and data collected were carried out, based on consultations to the relevant technical literature and applicable laws. The result of this study was the identification of the main risk factors in the work environment, with proposals for associated control measures, aiming at greater safety, health and comfort for dairy workers.